Diagnostic Accuracy and Pitfalls in Fine Needle Aspiration Cytology of Salivary Gland Lesions: An Advanced Study Approach - Crysle Saldanha; Hilda Fernandes (Recent Developments in Medicine and Medical Research Vol. 10, 2021)
Background: Fine Needle Aspiration cytology (FNAC) is an essential diagnostic method used to evaluate salivary gland lesions. However, at times, diverse morphological patterns and overlapping features between benign and malignant lesions becomes challenging and difficult to give a definitive diagnosis. Aims/Objectives: To compare the findings of preoperative FNAC with their histopathological types. To discuss the causes for discordancy and identify the potential pitfalls in cytological diagnosis. Materials and Methods: An observational analytical study was carried out over a 4-year period to review the cases of patients with salivary gland lesions who underwent FNAC in a medical college, hospital. Taking histopathological diagnosis as gold standard, the cytological diagnosis of the cases was compared and the causes of discrepancies were evaluated. Sensitivity, specificity, accuracy, positive predictive value and negative predictive value was calculated. Results: In the present study, out of 137 cases, cyto- histological correlation was available in 46 cases. Pleomorphic adenoma was the commonest lesion in the study. The diagnostic value of FNAC was: Sensitivity 66.7%, Specificity 97.4%, Positive Predictive Value 80%, Negative Predictive Value 95% and Diagnostic Accuracy 93.3%. False positive diagnosis was rendered in Warthin’s tumor whereas false negative diagnosis was given in mucoepidermoid carcinoma. Conclusion: FNAC is useful in the preoperative diagnosis of salivary gland lesions. Pitfalls in cytologic diagnosis were due to errors in sampling, cystic lesions and interpretation of smears. Accuracy depends on experience, and this method provides superior advantages for the clinicians and the patients.